2013
DOI: 10.1111/1753-0407.12025
|View full text |Cite
|
Sign up to set email alerts
|

Association study of genetic variants of 17 diabetes‐related genes/loci and cardiovascular risk and diabetic nephropathy in the Chinese She population (中国畲族人群17个糖尿病相关基因位点的遗传变异与心血管风险和糖尿病肾病的相关性)

Abstract: Variants in WFS1, CDKN2A/B, KCNJ11, CDC123/CAMK1D, JAZF1, SLC30A8, FTO, CDKAL1, and HHEX/IDE genes are significantly associated with T2DM in She Chinese subjects. JAZF1, FTO, CDKAL1, and HHEX/IDE are associated with diabetic nephropathy. WFS1, CDKN2A/B, CDC123/CAMK1D, JAZF1, FTO, CDKAL1, and HHEX/IDE are associated with cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…Eligible criteria included (1) candidate-gene association studies for T2DM published in peer-reviewed journal, (2) participants recruited from independent populations, (3) genotype information sufficient to calculate allele counts, (4) candidate genes tested in our study and (4) study population restricted to Han Chinese. A total of 21 studies that fulfill were indentified [13], [16][35]. Full-text manuscripts were obtained for all studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eligible criteria included (1) candidate-gene association studies for T2DM published in peer-reviewed journal, (2) participants recruited from independent populations, (3) genotype information sufficient to calculate allele counts, (4) candidate genes tested in our study and (4) study population restricted to Han Chinese. A total of 21 studies that fulfill were indentified [13], [16][35]. Full-text manuscripts were obtained for all studies.…”
Section: Methodsmentioning
confidence: 99%
“…Full-text manuscripts were obtained for all studies. One study was excluded because its study population was confined to She Chinese population[35]. Data extraction was performed and examined independently by two reviewers (YCC and YHY).All procedures were conformed to the Preferred Reporting Items for Systemic Review and Meta-Analysis (PRISMA) guidelines for meta-analysis[36].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have further shown the effects of the FTO gene on the risk of BMI-related outcomes such as diabetes [33], neural tube defects [33] and Alzheimer's disease [34]. Although the effects of obesity on the development of metabolic and cardiovascular problems are well studied, much less is known about its impact on the infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the expression of ZnT8 has been demonstrated to be decreased in the β cells of diabetic mice (19). A ZnT8 (or SLC30A8) gene polymorphism has been identified, and is associated with type 2 diabetes (20)(21)(22). Furthermore, an autoantibody to ZnT8 is widely considered as a biomarker of autoimmune diabetes (23,24).…”
mentioning
confidence: 99%